2019
DOI: 10.1089/lap.2019.0541
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy Analysis of the Combination of the Laparoscope and Preoperative or Intraoperative Duodenoscope in the Treatment of Cholecystolithiasis with Choledocholithiasis: A Retrospective Study

Abstract: Aim: This study aims to analyze the efficacy and safety of the combination of laparoscope and preoperative (PODL) or intraoperative (IODL) duodenoscope in the treatment of cholecystolithiasis with choledocholithiasis. Materials and Methods: From January 2015 to February 2017, 51 patients with cholecystolithiasis and choledocholithiasis, who were treated with the PODL (n = 29) or IODL (n = 22), were reviewed retrospectively. The efficacy and safety were evaluated and compared between these two groups. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…What is more, the therapeutic effect of the biliary function index of the AI group was also much better than that of the conventional group. The above results are consistent with most other complication rates after treatment with laparoscopy combined with duodenoscope for treatment of gallbladder stones combined with common bile duct stones [4,5,[26][27][28], providing support for laparoscopy combined with duodenoscope in the treatment of gallstones. Of course, AI-assisted visual sensing technology shows a wide range of applications, not just for assisted endoscopic treatment of gallbladder stones, which has been illustrated in a number of studies on the optimization of colonoscopy bowel preparation and the establishment and preliminary verification of the artificial intelligence-assisted colorectal polyp identification system [29][30][31][32].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…What is more, the therapeutic effect of the biliary function index of the AI group was also much better than that of the conventional group. The above results are consistent with most other complication rates after treatment with laparoscopy combined with duodenoscope for treatment of gallbladder stones combined with common bile duct stones [4,5,[26][27][28], providing support for laparoscopy combined with duodenoscope in the treatment of gallstones. Of course, AI-assisted visual sensing technology shows a wide range of applications, not just for assisted endoscopic treatment of gallbladder stones, which has been illustrated in a number of studies on the optimization of colonoscopy bowel preparation and the establishment and preliminary verification of the artificial intelligence-assisted colorectal polyp identification system [29][30][31][32].…”
Section: Discussionsupporting
confidence: 83%
“…It refers to the method of pulling the bile duct stones out of the bile duct using net baskets, balloons, and other instruments under a duodenoscope. The main indications are choledocholithiasis, hepatolithiasis, and gallbladder stones [5]. Laparoscopy is mostly used to guide gallbladder resection.…”
Section: Introductionmentioning
confidence: 99%
“…A single case study reported that this combination procedure is safe for patients with gallstones; these patients are unlikely to experience postoperative complications, such as bleeding, bile leakage, or pancreatitis and recover well three months after surgery[ 15 ]. In another study, compared with preoperative duodenoscopy, laparoscopy combined with intraoperative duodenoscopy for patients with cholecystolithiasis combined with choledocholithiasis had a higher success rate, caused less pain, and required a shorter hospital stay[ 16 ].…”
Section: Introductionmentioning
confidence: 99%